2022
DOI: 10.3390/ijms231911391
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA Repair in Neurodegenerative Diseases and Ageing

Abstract: Mitochondria are the only organelles, along with the nucleus, that have their own DNA. Mitochondrial DNA (mtDNA) is a double-stranded circular molecule of ~16.5 kbp that can exist in multiple copies within the organelle. Both strands are translated and encode for 22 tRNAs, 2 rRNAs, and 13 proteins. mtDNA molecules are anchored to the inner mitochondrial membrane and, in association with proteins, form a structure called nucleoid, which exerts a structural and protective function. Indeed, mitochondria have evol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 162 publications
0
15
0
Order By: Relevance
“…Mitochondrial infusion has shown great potential both preclinically and clinically [ 125 ]. An increasing number of studies have attempted to improve mitochondrial function in aging and age-related diseases [ 126 ]. From these attempts, methods involving mitochondrial isolation, blood transfusion and transplantation have become the focus of attention.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Mitochondrial infusion has shown great potential both preclinically and clinically [ 125 ]. An increasing number of studies have attempted to improve mitochondrial function in aging and age-related diseases [ 126 ]. From these attempts, methods involving mitochondrial isolation, blood transfusion and transplantation have become the focus of attention.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Secondly, the α-synuclein accumulation in the brainstem is also a mechanism contributing to the pathogenesis of iRBD. Melatonin can reduce the aggregation of α-synuclein and exerts neuroprotective effects by scavenging free radicals ( 84 , 85 ), stimulating glutathione synthesis ( 86 , 87 ), enhancing antioxidant enzyme synthesis, and inhibiting the production of pro-oxidant enzymes ( 88 , 89 ), thus alleviating α-synuclein’s mitochondrial toxicity ( 90 , 91 ). Thirdly, studies have reported that inflammation plays a role in the pathogenesis of iRBD ( 92 , 93 ).…”
Section: Discussionmentioning
confidence: 99%
“…At the neuronal level, these cytokines cause a drop in serotonin, dopamine and adrenaline neurotransmitters that triggers a neuroinflammatory phenotype. Moreover, oxidative stress and consequent mitophagy sustain the neuroinflammation, accompanied by a leakage of mitochondrial DNA (mtDNA) from damaged mitochondria that physiologically tends to gradually increase with age, contributing to the so-called inflammaging [ 159 , 160 ]. In addition, the similarity between mtDNA and bacterial DNA and its oxidized state stimulates the immune response and promotes inflammation.…”
Section: Ros Mitochondria and Neurodegenerative Diseasesmentioning
confidence: 99%